2015
DOI: 10.1007/s40266-015-0286-5
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacist–Physician Intervention Model Using a Computerized Alert System to Reduce High-Risk Medication Use in Elderly Inpatients

Abstract: The intervention model reduced high-risk medication use in older inpatients. Most of the vulnerable inpatients identified by CAS alerts would not have otherwise had a geriatric medication review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…* Some of the studies are underpowered to detect a difference and do not show statistically significant outcomes. 31,33,56,69,70,72 Psychiatric pharmacists also show statistically significant benefits on patient-level outcomes in at least 5 peer-reviewed publications by providing services, including medication reviews, patient education, à patient and/or data evaluation for medication safety and efficacy, 26,31,35,37,40,41,47 and independent management of medication therapy upon referral. 50,[76][77][78][79]81 Twenty (31.3%) of the included studies have at least 1 BCPP author with formal advanced training in psychiatry/ neurology.…”
Section: Resultsmentioning
confidence: 99%
“…* Some of the studies are underpowered to detect a difference and do not show statistically significant outcomes. 31,33,56,69,70,72 Psychiatric pharmacists also show statistically significant benefits on patient-level outcomes in at least 5 peer-reviewed publications by providing services, including medication reviews, patient education, à patient and/or data evaluation for medication safety and efficacy, 26,31,35,37,40,41,47 and independent management of medication therapy upon referral. 50,[76][77][78][79]81 Twenty (31.3%) of the included studies have at least 1 BCPP author with formal advanced training in psychiatry/ neurology.…”
Section: Resultsmentioning
confidence: 99%
“…A pharmacist reviewed the CAS alerts, evaluated their clinical relevance, analyzed the individual's pharmacotherapy, and developed a geriatric phamacotherapeutic plan to be discussed with the treating physician. In a pilot study, conducted at one of the two CHUS sites, the clinical relevance of the alerts was 74.5%, and the interventions led to a change in at least one targeted medication in 77.7% of the interventions …”
Section: Methodsmentioning
confidence: 99%
“…In a pilot study, conducted at one of the two CHUS sites, the clinical relevance of the alerts was 74.5%, and the interventions led to a change in at least one targeted medication in 77.7% of the interventions. 27…”
Section: Computerized Systemmentioning
confidence: 99%
“…2 As one example, Quebec-based pharmacists demonstrated that a computerized review of individual patients' health care records using selected Beers criteria could identify patients for whom inappropriate medications had been prescribed. 3 In that study, computerization of patient screening allowed the pharmacists to efficiently identify patients at risk of ADRs and intervene to adjust their therapy.…”
Section: Editorial Protecting Our Elderly Patients From Adverse Drug mentioning
confidence: 99%